СОВЕРШЕНСТВОВАНИЕ ГОСУДАРСТВЕННОГО РЕГУЛИРОВАНИЯ АГРАРНОГО РЫНКА ТРУДА (НА ПРИМЕРЕ АКМОЛИНСКОЙ ОБЛАСТИ) (Экономика: стратегия и практика, 2019)
In the conditions of market relations, it is important to explore the labor market as a socio-economic phenomenon, considering it from a theoretical point of view, which requires an understanding of the socio-economic nature of the labor market. The object of the labor market is labor, and the labor bearer - labor force - labor resources, which are characterized by such basic indicators as employment and unemployment.The research consisted of the works of domestic and foreign leading economists. In the course of the study, the author applied methods of system, comparative, factor analysis, as well as methods of statistical analysis of economic processes. In the course of carrying out the work, the author used general methodological principles that made it possible to most fully and objectively investigate problems.The labor market of Kazakhstan at the present stage is significantly different from labor markets in other countries due to its underdevelopment, which was facilitated by a number of reasons, such as difficulties in trans-forming the social and political system, lack of experience in institutionalizing market transformations, etc. These difficulties predetermined the problems of the modern labor market of Kazakhstan, associated with poor social protection of the unemployed, a high proportion of informal and shadow employment, low labor mobility resources, an increase in the share of non-specialty citizens and some others.